De-welding of thermoplastic composites: next step in sustainable joints - Vos, C.J. de; Obbink, M.; Sterk, S.; Erartsin, O.; Jong, M. de (My University, 2024)
“De-welding” of welded joints offer the prospect of repositioning the welded parts due to assembly errors, or removing a damaged part for repair or recycle; contributing to more sustainable manufacturing and assembly of aerospace components. In this study, feasibility of resistance heating for de-welding of thermoplastic composites is investigated at coupon level, along with the processing window required for de-welding. For coupon tests, multidirectional C/LM-PAEK adherends were co-consolidated in single lap shear (SLS) configuration with LMPAEK or PEI based carbon fabric reinforced prepreg heating element and glass fabric reinforced insulators between them. In coupon de-welding tests, shear load was applied after the interfaces of the SLS coupons were heated to various de-welding temperatures. Coupon tests, and subsequently microscopic analysis, showed that thermoplastic composites can successfully be de-welded by resistance heating without introducing damage to adherends. Low de-welding forces were obtained above the melting and glass transition points of LM-PAEK and PEI based heating elements, respectively. PEI based heating element significantly reduced the temperature required for de-welding.